Religion, violence & the state : a dialogical encounter between activists and scholars - Omar, Abdul Rashied (Department of Religious Studies, 2014)
This dissertation places the voices of three leading religious activists in juxtaposition to comtemporary scholarship on relition and violence in the Western acady. It highlights a neglected issued in that body of scholarship, namely the link between systemic violence and state terror. I raise three interratled research questions: First how does the post-Cold War literature on religion and violence deal with the issue of systemic institutional violence and state-sponsored terror as elucidated by Chomsky and Herman (1979), Stohl and Lopez (1984), Falk (1998) and Sluka (2000)? Second, under what conditions and through which mechanisms are religious discourses and actors enlisted in legitimating the state's resort to violence? Third, what kinds of theory are tangibly present in the growing field of study on religion and violence and to what extent are these theories challenging or serving the interests of state authorities? I employ two research methods. The first is a critical textual hermeneutics applied to both primary sources on religion, violence and the state found within religious institutions, such as sermons, press articles, etc., as well as the burgeoning scholarly literature on relition and violence that has emerged since 1989. The second involves conducting a number of qualitative interview with three renowned religious activists from diverse contexts who lived, theologized, and theorized in the midst of situations of deadly conflict. For this dissertation I have chosen Michael Lapsley of South Africa, Mustafa Ceric of Bosnia-Herzegovina, and Swami Agnivesh of India. The three case studies I have examined accentuate different aspects of religion and violence nexus but have one key thing in common: all three point to the critical role of the state, and in particular illuminate the manner in which religion can buttress and sanctify state-sponsored violence.